Analogy versus explicit learning of a modified basketball shooting task: Performance and kinematic outcomes - Lam, W. K.; Maxwell, J. P.; Masters, R. S. W. (Journal of Sports Sciences, 2009)
The effects of differential instructional sets on motor skill acquisition were investigated using performance outcome and kinematic measures. Participants were provided with a single analogical instruction (analogy learning), a set of eight explicit (technical) instructions (explicit learning), or were not instructed (control). During a learning phase, participants (n = 9 for each condition) performed a modified basketball shooting task over 3 days (160 trials per day). On the fourth day, participants performed a test phase consisting of two 40-trial retention tests, separated by a 40-trial secondary task transfer test, and completed a verbal protocol describing in detail the techniques that they had used to perform the task. No performance differences were found during the two retention tests, indicating similar amounts of learning for all groups. During the transfer test, performance deteriorated for both the explicit and control conditions, but not for the analogy condition. Participants in the analogy condition reported significantly fewer technical rules. Although no group differences were reported for kinematic variables, identification of movement components supported the claim that explicit learners exert conscious control over their movements, whereas analogy learners use a more implicit (unconscious or automatic) mode of movement control.